METODE BERCERITA PADA PEMBELAJARAN SEJARAH KEBUDAYAAN ISLAM (SKI) DI MADRASAH IBTIDAIYAH - Zumrotus Sa’diyah; Firda Zakiyatur Rofiah (Universitas Islam Sumatera Utara, 2020)
Studying the history of Islamic culture cannot be separated from the role of the teacher in transferring effective learning. One of the methods used in learning the history of Islamic culture is the storytelling method. For teachers who have the expertise possessed by teachers of Islamic cultural history in delivering subject matter to students so that students become enthusiastic in listening to it. As a result, the students were moved by the story. The study of this research uses literature review by collecting books, journals. The results showed that the skills in storytelling for SKI teachers, which so far have been considered a boring subject, in essence are not so dependent on the competence of teachers in teaching and classroom management.